Constitutional Democracy in Globalization Dimension: the Causes of Erosion and Prospects for Changes - A. N. Medushevsky (Теоретическая и прикладная юриспруденция)
The globalization process provoked the deep transformation of international law, political affairs and governance with controversial consequences. From the one hand, it stimulated the cosmopolitan project of global constitutionalism — transnational integration and unification of democratic standards; from the other hand, it resulted in fragmentation of international affairs, deterioration of constitutional democracy and the feeling of democracy deficits on national and international level of governance. Trying to balance the impact of these opposite trends, the author analyses positive and negative effects of globalization on constitutional development regarding such issues as transnational constitutionalization, democracy and national sovereignty, the changing place of multilayer constitutionalism, separation of powers, and system of global governance in the establishment of transnational constitutional democratic legitimacy.